Role of High-sensitivity Cardiac Troponin in Acute Coronary Syndrome - Mahesh Anantha Narayanan (Radcliffe Medical Media, 2019)
Chest pain is one of the most common reasons for an emergency room (ER) visit in the US, with almost 6 million ER visits annually. High-sensitivity cardiac troponin (hscTn) assays have the ability to rapidly rule in or rule out acute coronary syndrome with improved sensitivity, and they are increasingly being used. Though hscTn assays have been approved for use in European, Australian, and Canadian guidelines since 2010, the FDA only approved their use in 2017. There is no consensus on how to compare the results from various hscTn assays. A literature review was performed to analyze the advantages and limitations of using hscTn as a standard biomarker to evaluate patients with suspected ACS in the emergency setting.